Travel characteristics and mobility constraints of the elderly in Ibadan, Nigeria (2010)
The paper assessed the travel characteristic and mobility crisis of the elderly in Ibadan Metropolis. A sample of 264 elderly people completed a questionnaire survey. Tables of percentages, graphs and chi-square were used for data presentation. Findings showed that 60.3% of the respondents were married, 70.3% had no more than secondary education and over 50% earned less than N20,000 per month mainly from working and remittances. Work and health related trips accounted for 31.8% and 27.1% of the journey purpose. Similarly, the use of bus and walking accounted for 30% and 29.6% of the modal split. Chi-square analysis indicated significant variations in terms of travel time and transport cost in the three density zones. Vehicle design, long access and waiting time as well as poor facilities at the terminals were identified as constraints to the effective mobility of the elderly. The paper identified both short and long term measures for ameliorating the mobility crisis and transport burden of the elderly in Ibadan Metropolis.